Where and When: Sharpening the lens on geographic disparities in mortality - Wei Xu; Michal Engelman; Alberto Palloni; Jason Fletcher (Elsevier, 2020)
Life course theories suggest that geographic disparities in mortality may reflect a history of place-based exposures rather than (or in addition to) contemporaneous exposures; yet, few studies examined early life place exposures and later life mortality in the US due to data limitations. The aim of this study is to assess and compare the importance of state of birth and state of residence in predicting mortality for adults over age 50 in the US. Using nationally representative data of nearly 100,000 adults over age 50 from the National Longitudinal Mortality Study, we estimated individual mortality risk using multi-level logistic regression with state of birth and state of residence as second-level random effects. We assessed whether state of residence and state of birth contributed to the variation in adult mortality. We also decomposed state-of-residence random effects to compare "movers" and "stayers." Our results indicate that state of birth is a stronger predictor of age-, race/ethnicity- and sex-adjusted mortality in the US than state of residence at the time of death. The adult mortality profiles of many states are substantially impacted by the composition of "movers." Failing to account for residential mobility has clouded our understanding of the patterns and causes of geographic differences in adult mortality. Measures of geographic residence across the life course can improve models of adult mortality in the US and inform interventions to address geographic disparities in longevity.